Music and Democracy Participatory Approaches - Kölbl, Marko; Trümpi, Fritz (mdwPress, 2021)
Music and Democracy explores music as a resource for societal transformation processes. This book provides recent insights into how individuals and groups used and still use music to achieve social, cultural, and political participation and bring about social change. The contributors present outstanding perspectives on the topic: From the promise and myth of democratization through music technology to the use of music in imposing authoritarian, neoliberal or even fascist political ideas in the past and present up to music's impact on political systems, governmental representation, and socio-political realities. The volume further features approaches in the fields of gender, migration, disability, and digitalization.